การศึกษาเปรียบเทียบกระบวนการนิติบัญญัติระหว่างสาธารณรัฐประชาธิปไตยประชาชนลาว กับราชอาณาจักรไทย - สิงห์คำ วงพระจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Legislation processes is a process stipulating the action of human being in the society or a measure of committing in society. The legislation has been utilized to govern citizen in the state as well as a significant provision for people live together in society. The legislation processes is consist of submitting consideration and approval law. Each process has various organs and institution that have function stipulating in the constitution. Law therefore has been established suitable for social – economic development, political and national stability. The performance of the law has whether or not justice for citizens depending on organs and institution that have functioned concerned in consideration justice for the highest achievement. In this regards, it requires to mobilize profound knowledge in systematic to meet the demand of that situation by creating facilitate and interest for citizens. The reason is that the provision of the law has been stipulated can be brought into practice and make justice for general citizens. This thesis a comparative study of legislation process of the Lao PDR and Thailand found that in principle, the legislation processes has similarity procedure and mythology but it is quite different in detail. This research found that legislation processes of the Lao PDR has committed in the short period the committing has been become the weak point of legislation processes in particular submitting consideration and approval law including the role of authorities concerned with legislation process which will impact the effective law that has been issued for implementation in society. In this matter, the author advices the matter of situation and the direction for improvement in order to make appropriate legislation process of Lao PDR to equivalent with international standard.